Clinical Value and Underlying Mechanisms of Upregulated LINC00485 in Hepatocellular Carcinoma - Zhu, Xinyu; Feng, Yanlin; He, Dingdong; Wang, Zi; Huang, Fangfang; Tu, Jiancheng (Frontiers in Oncology, 2021)
Aims: This study aimed to reveal the functional role of LINC00485 in hepatocellular carcinoma (HCC). Materials & Methods: 210 serum samples from Zhongnan Hospital of Wuhan University were employed to evaluate clinical value of LINC00485. Bioinformatics analysis was adopted to explore its potential mechanisms. Results: LINC00485 was confirmed to be upregulated in HCC tissues and serum samples. Survival analysis and receiver operating characteristic curve revealed its prognostic and diagnostic roles. The combination of serum LINC00485 with AFP can remarkably improve diagnostic ability of HCC. Exploration of the underlying mechanism demonstrated that LINC00485 might exert pro-oncogenic activity by LINC00485—three miRNAs—four mRNAs network. Conclusions: our study unveiled that upregulated LINC00485 could act as a potential diagnostic and prognostic biomarker and provide a novel insight into the molecular mechanisms of LINC00485 in HCC pathogenesis.